2D/3D Microanalysis by Energy Dispersive X-ray Absorption Spectroscopy Tomography. Issue 1 (December 2017) - Sanchez, Dario; Simionovici, Alexandre; Lemelle, Laurence; Cuartero, Vera; Mathon, Olivier; Pascarelli, Sakura; Bonnin, Anne; Shapiro, Russell; Konhauser, Kurt; Grolimund, Daniel; Bleuet, Pierre
Abstract X-ray spectroscopic techniques have proven to be particularly useful in elucidating the molecular and electronic structural information of chemically heterogeneous and complex micro- and nano-structured materials. However, spatially resolved chemical characterization at the micrometre scale remains a challenge. Here, we report the novel hyperspectral technique of micro Energy Dispersive X-ray Absorption Spectroscopy (μED-XAS) tomography which can resolve in both 2D and 3D the spatial distribution of chemical species through the reconstruction of XANES spectra. To document the capability of the technique in resolving chemical species, we first analyse a sample containing 2–30 μm grains of various ferrous- and ferric-iron containing minerals, including hypersthene, magnetite and hematite, distributed in a light matrix of a resin. We accurately obtain the XANES spectra at the Fe K-edge of these four standards, with spatial resolution of 3 μm. Subsequently, a sample of ~1.9 billion-year-old microfossil from the Gunflint Formation in Canada is investigated, and for the first time ever, we are able to locally identify the oxidation state of iron compounds encrusting the 5 to 10 μm microfossils. Our results highlight the potential for attaining new insights into Precambrian ecosystems and the composition of Earth's earliest life forms.